Ageism in a health-related context: the physiological, psychological, and behavioral impacts of subtle age discrimination on older adults - Linnea C. Ng; Hannah J. Kim; Mikki Hebl; Eden B. King; Christopher P. Fagundes (Scientific Reports)
Abstract Older adults are a rapidly increasing demographic in the U.S. whose longevity depends on high quality healthcare. Unfortunately, older adults often face ageism in healthcare settings. Ageism involves not only explicit age discrimination (e.g., refusal to engage with older adults due to a stated dislike), but also more subtle age discrimination (e.g., systematic avoidance of eye contact with older adults). Both forms of age discrimination are largely underexplored in medical settings. Furthermore, it is unclear what impact subtle age discrimination has on health-related outcomes. This study examines the effects of subtle age discrimination on the experiences of older adults in healthcare-related interactions. Through scripted interactions between researchers and participants (65 + years of age), we found negative biopsychosocial impacts of subtle age discrimination on older adults; subtle age discrimination led to substandard physiological (i.e., lowered HRV), psychological (i.e., reduced trust), and behavioral (i.e., increased avoidance of future interactions) outcomes. Increasing awareness and recognition of age discrimination in health-related settings is critical for ensuring that older adults can navigate a more optimal healthcare system that improves rather than compromises older adults’ health.